Plasticity Induced by Intermittent Theta Burst Stimulation in Bilateral Motor Cortices Is Not Altered in Older Adults. (6th May 2015) - Dickins, Daina S. E.; Sale, Martin V.; Kamke, Marc R.
Abstract : Numerous studies have reported that plasticity induced in the motor cortex by transcranial magnetic stimulation (TMS) is attenuated in older adults. Those investigations, however, have focused solely on the stimulated hemisphere. Compared to young adults, older adults exhibit more widespread activity across bilateral motor cortices during the performance of unilateral motor tasks, suggesting that the manifestation of plasticity might also be altered. To address this question, twenty young (<35 years old) and older adults (>65 years) underwent intermittent theta burst stimulation (iTBS) whilst attending to the hand targeted by the plasticity-inducing procedure. The amplitude of motor evoked potentials (MEPs) elicited by single pulse TMS was used to quantify cortical excitability before and after iTBS. Individual responses to iTBS were highly variable, with half the participants showing an unexpected decrease in cortical excitability. Contrary to predictions, however, there were no age-related differences in the magnitude or manifestation of plasticity across bilateral motor cortices. The findings suggest that advancing age does not influence the capacity for, or manifestation of, plasticity induced by iTBS.